2011
DOI: 10.1042/bst0391387
|View full text |Cite
|
Sign up to set email alerts
|

Non-homologous end-joining partners in a helical dance: structural studies of XLF–XRCC4 interactions

Abstract: XRCC4 (X-ray cross-complementation group 4) and XLF (XRCC4-like factor) are two essential interacting proteins in the human NHEJ (non-homologous end-joining) pathway that repairs DNA DSBs (double-strand breaks). The individual crystal structures show that the dimeric proteins are homologues with protomers containing head domains and helical coiled-coil tails related by approximate two-fold symmetry. Biochemical, mutagenesis, biophysical and structural studies have identified the regions of interaction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 30 publications
5
65
0
Order By: Relevance
“…We propose a speculative yet plausible explanation for this intriguing observation, based on our recent report on the Cernunnos-Xrcc4 complex structure (27). Crystals of Cernunnos-Xrcc4 complexes revealed that both homodimers associate with each other in long filaments through their head domains, helping to tether the broken DNA ends by creating a "DNA ligation synapse" (27)(28)(29)(30). The absence of Cernunnos would then result in DNA ligation synapse destabilization rather than a catalytic malfunction of the Xrcc4-Cernunnos-DNA ligase IV complex per se.…”
Section: Discussionmentioning
confidence: 99%
“…We propose a speculative yet plausible explanation for this intriguing observation, based on our recent report on the Cernunnos-Xrcc4 complex structure (27). Crystals of Cernunnos-Xrcc4 complexes revealed that both homodimers associate with each other in long filaments through their head domains, helping to tether the broken DNA ends by creating a "DNA ligation synapse" (27)(28)(29)(30). The absence of Cernunnos would then result in DNA ligation synapse destabilization rather than a catalytic malfunction of the Xrcc4-Cernunnos-DNA ligase IV complex per se.…”
Section: Discussionmentioning
confidence: 99%
“…Since its discovery in 2005, several functions have been described for XLF. It stimulates LIG4 activity, 21,22 and it can form long filaments with XRCC4 that keep the DNA ends together in a ligation synapse, 24,[48][49][50][51] and XLF is essential for gap-filling by polymerase (pol) l and polm during NHEJ. The latter function is interesting, as poll and polm belong to the same polX family of polymerases as For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…There, in ring-forming SAS-6, invariably exists a small amino acid residue, typically glycine or alanine. In contrast, in the spiral forming CeSAS-6 this position is occupied by a valine ( Figure 5); a valine is also found at the hinge position of XRCC4, which forms spirals similar to CeSAS-6 [32,[34][35][36]. The steric effect imposed by the valine in CeSAS-6 moves the coiled-coil helix relative to the N-terminal domain by approximately 40° compared to other SAS-6 variants [30], thereby driving successive CeSAS-6 dimers out of the horizontal plane and into a steep spiral of ~30 nm pitch.…”
Section: Sas-6 Spiralsmentioning
confidence: 93%
“…The SAS-6 N-terminal domain bears strong structural resemblance to similar domains of XRCC4 and XLF (Figure 2), proteins involved in DNA repair and non-homologous end joining. Further, similar to SAS-6, XRCC4 forms dimers via a coiled-coil domain, and it hetero-oligomerises with XLF via the globular N-terminal domains to form a spiral [32][33][34][35][36]. Most SAS-6 oligomers resolved to date are highly reminiscent of cartwheel rings, with a central hub derived from the N-terminal globular domains and the SAS-6 coiled coils comprising the cartwheel spokes [28,29,31].…”
Section: Introductionmentioning
confidence: 99%